2013
DOI: 10.1002/ejlt.201200418
|View full text |Cite
|
Sign up to set email alerts
|

Batch and continuous lipase‐catalyzed interesterification of blends containing olive oil for trans‐free margarines

Abstract: The interesterification of natural fats can improve certain physical and nutraceutical properties by modification of their acylglycerol profile. The aim of this study was the production of structured lipids by lipase-catalyzed interesterification of blends of palm stearin (PS), palm kernel oil (PK), and olive oil (OO), to be incorporated in margarines. Interesterification activity was evaluated by the decrease of the solid fat content at 358C (SFC 358C ) of the blends. The best interesterification conditions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…In human breast milk, PA constitutes the majority of saturated FAs at the sn ‐2 position at over 60% by weight . PA and SA are major contributors to obesity and hyperlipidemia . Therefore, the aim of this work was to reduce the PA and SA content at the sn ‐1,3 positions of silkworm pupae oil by replacement with monounsaturated fatty acids to yield products suitable for human consumption.…”
Section: Resultsmentioning
confidence: 99%
“…In human breast milk, PA constitutes the majority of saturated FAs at the sn ‐2 position at over 60% by weight . PA and SA are major contributors to obesity and hyperlipidemia . Therefore, the aim of this work was to reduce the PA and SA content at the sn ‐1,3 positions of silkworm pupae oil by replacement with monounsaturated fatty acids to yield products suitable for human consumption.…”
Section: Resultsmentioning
confidence: 99%
“…Fat crystals in the β′ form are smaller and of a lower melting point (Sato, 2001b), properties that impart a smooth texture to the product. As can be seen from blends of OO, PKO, and PS have been interesterified by using sn-1,3-specific lipases (Lipozyme TL IM and Lipozyme RM IM) in order to produce TFA-free margarines (De Martini Soares et al, 2013). This effect increases, in turn, the miscibility between the fat hardstock and liquid oil TAGs, resulting in the formation of mixed crystals and a more homogeneous and tight fat crystal network, with enhanced stabilization and texture properties.…”
Section: Saturated Fatty Acids Content (%)mentioning
confidence: 99%
“…Furthermore, the analysis of TAG composition of the PS:SO blend demonstrated that the interesterification process catalyzed by Pseudomonas lipase, results in the formation of mixed-acid TAGs with randomized FA. The interesterified blend comprising 25% OO, 30% PKO, and 45% PS produced a randomized FA composition in the TAGs, resulting in an increased intersolubility in the TAGs of the lipid phase (De Martini Soares et al, 2013). Olive oil is obtained by mechanical extraction of the fruit of the olive tree (Olea europea L. tree) (IOOC, 1993).…”
Section: Saturated Fatty Acids Content (%)mentioning
confidence: 99%
See 2 more Smart Citations